IMPLEMENTASI GOOD ZAKAT GOVERNANCE BERDASARKAN PSAK (SAS) 109 DAN PRINSIP INTI ZAKAT PADA BADAN AMIL ZAKAT NASIONAL - Shafira Nurjanah (2023)
This study uses a qualitative method which aims to find out the alignment of the implementation of good zakat governance based on PSAK 109 and the zakat core principles of the RI National BAZNAS on operational aspects of the RI National BAZNAS. Based on the author's observations, it is found that many people do not want to distribute their zakat to zakat management organizations. This study uses qualitative methods and adapts to interpretive paradigms and phenomenological approaches. This research focuses on how the informants interpret PSAK 109 as well as the Zakat Core Principle empirically, also examines the construction of reality that is described by individuals during their daily activities at the research location. Based on the Zakat Core Principle, it has been implemented properly and is in accordance with existing principles. The implementation of Good Zakat Governance has been well implemented according to the principles set out in the GZG. Submission of information, reports, and supervision that is carried out properly in accordance with existing rules has been carried out properly. Disclosure, Acknowledgment of Measurement and Presentation in Financial Statements are in accordance with PSAK 109, and BAZNAS has no problems in implementing PSAK 109, also all components in PSAK 109 have been implemented properly by BAZNAS. BAZNAS also received a Fair Opinion Without Control by the Auditor at the Public Accounting Firm that audited it. For the core principles of zakat have also been implemented properly, so as to create good zakat governance.